2006
DOI: 10.2203/dose-response.004.01.003.akirav
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Determine the Non-Linear Amygdala Influence on Hippocampus-Dependent Memory

Abstract: ᮀ Stressful experiences are known to either improve or impair hippocampal-dependent memory tasks and synaptic plasticity. These positive and negative effects of stress on the hippocampus have been largely documented, however little is known about the mechanism involved in the twofold influence of stress on hippocampal functioning and about what factors define an enhancing or inhibitory outcome. We have recently demonstrated that activation of the basolateral amygdala can produce a biphasic effect, enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 104 publications
(147 reference statements)
0
21
0
1
Order By: Relevance
“…Furthermore, the same argument can be applied to cues predicting food intake. In this article, we will consequently develop the hypothesis that the amygdala is involved (1) in the relevance processing of food stimuli, including (2) in the detection of cues linked to food intake. Additionally, we will present its role in (3) stress-induced eating, and briefly mention (4) its uncertain role in satiety signals.…”
Section: Summary Of Early Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the same argument can be applied to cues predicting food intake. In this article, we will consequently develop the hypothesis that the amygdala is involved (1) in the relevance processing of food stimuli, including (2) in the detection of cues linked to food intake. Additionally, we will present its role in (3) stress-induced eating, and briefly mention (4) its uncertain role in satiety signals.…”
Section: Summary Of Early Clinical Evidencementioning
confidence: 99%
“…Third, cued conditioning relies on the amygdala, but in the case of a conditioning relying on context, the hippocampus would additionally be recruited [97]. Fourth, a lot of studies have shown that a stimulation of the amygdala enhances hippocampal-dependent memory and modulates the synaptic plasticity in the hippocampus (e.g., [1,2,40,69,93,100,102,104]). Fifth, learning to suppress conditioned responses requires interactions between the hippocampus and the (basolateral) amygdala.…”
Section: Interactions Between the Amygdala And The Hippocampusmentioning
confidence: 99%
“…It is also well-established that stress reduces hippocampal expression of brain-derived neurotrophic factor (BDNF), which has been associated with impaired hippocampus-dependent memory (Radecki et al, 2005;Duman and Monteggia, 2006). In contrast, stress or a fear-provoking experience activates molecular plasticity in the amygdala (Pare, 2003;Monfils et al, 2007;Ilin and Richter-Levin, 2009), which exerts an inhibitory influence on hippocampal plasticity (Akirav and Richter-Levin, 1999;Akirav and Richter-Levin, 2006). Therefore, understanding how stress differentially affects molecular plasticity in the hippocampus, amygdala and PFC could enhance our understanding of the complexity of how stress affects learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus is one of the memoryrelated targets of these actions, being specifically susceptible to uncontrollable stress through a pathway that involves the amygdala (Kim and Diamond 2002;Akirav and Richter-Levin 2006;Malin and McGaugh 2006). Several convergent studies show that either corticosterone, or the synthetic glucocorticoid dexamethasone, or stress promote the enhancement of memory consolidation (Roozendaal and McGaugh 1996;Roozendaal et al 1999) while impairing retrieval (de Quervain et al 1998;Roozendaal et al 2003).…”
mentioning
confidence: 99%